Clinician and administrator perspectives on outpatient administration of ciltacabtagene autoleucel in relapsed or refractory multiple myeloma - Hansen, Doris K.; Dhakal, Binod; Hamadani, Mehdi; Dingli, David; Jain, Tania; Huff, Carol Ann; Janakiram, Murali; Liu, Yi-Hsuan; De Braganca, Kevin C.; Lodowski, Nicole; Sander, Jennifer; Okorozo, Peter; et al. (Frontiers in Immunology, 2024)
Introduction Chimeric antigen receptor (CAR) T-cell therapy (CAR T therapy) is a treatment option for patients with relapsed or refractory multiple myeloma that has led to unprecedented treatment outcomes. Among CAR T therapies available, ciltacabtagene autoleucel (cilta-cel) is a good candidate for outpatient administration due to its generally predictable safety profile. There are multiple advantages of outpatient administration of cilta-cel, including reduced healthcare burden, expanded access, and patient autonomy. This mixed methods qualitative study aimed to identify key factors for outpatient administration of CAR T and best practice recommendations by combining a targeted literature review with expert interviews and panels. Methods The targeted review (Phase 1) aimed to identify factors for outpatient CAR T administration in the US and determine key topics for the exploratory interviews (Phase 2) and expert panels (Phase 3), which aimed to inform on best practices and challenges of outpatient CAR T administration (focusing on cilta-cel). Participants in clinical and administrative positions based in treatment centers that had experience with real-world outpatient administration of cilta-cel were recruited. Results Seventeen studies were identified in Phase 1. Key factors for outpatient administration included the development of protocols for CAR T complications, education for caregivers, outpatient specialists, hospital staff, and emergency services staff for identification and referral after possible adverse events, the creation of multidisciplinary teams for effective communication and management, straightforward patient intake processes encompassing financial eligibility review and provision of patient education materials, and close patient monitoring throughout the treatment journey. In Phase 2, 5 participants from 2 centers were interviewed. In Phase 3, 14 participants across 6 treatment centers were interviewed. Two 90-minute virtual panel discussions took place. All participants agreed that cilta-cel can be safely and effectively administered in an outpatient setting. Key recommendations included the creation of educational resources for patients and caregivers, the development of standard operating procedures, dedicated outpatient infrastructure and establishment of interdisciplinary teams, outpatient monitoring for toxicity management, and monitoring of the reimbursement landscape. Discussion This study offers a comprehensive understanding of the feasibility of outpatient cilta-cel administration in participating CAR T centers and provides actionable recommendations while acknowledging existing challenges.